(untitled) (Revista LIDER, 2019)
This work is part of a larger study that investigates wolf watching tourism in the Sierra de la Culebra, in Zamora, Spain. We have analyzed the meanings that tourists associate with the animal in this area, and three spheres of interrelated meaning have been specified: the natural world, human society and the spiritual world. The wolf appears as a "special animal" to which positive meanings of harmony and resistance of the natural world, social renewal, purity and authenticity, are linked. In addition, the sociocultural changes produced by wolf observation tourism are analyzed, paying special attention to the local perception of the predator. Methodologically, this work is approached from an anthropological perspective and through qualitative methodology, during the years 2013- 2017. With a technique of ethnographic work, the participant observation has been given great weight. In addition, semi-structured interviews aimed at 100 informants have been conducted. It is concluded that the observation of wolves in the Culebra, planned and normalized, can be an activity that favors sustainable tourism that contributes both to the conservation of the wolf and the environment, and to the improvement of the opportunities of the weak economic sector in the area.